Sosialisasi Pentingnya Gizi Seimbang Dan Pola Asuh Guna Meningkatkan Kualitas Gizi Menuju Generasi Unggul - Nasrulloh, Muhammad Farid; Zidan, Zainuddin Azizun; Khuzaini, Nanang; Zuhriawan, Muhammad Qoyum; Hidayatulloh, Faisol; Khotimah, Khusnul (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2025)
Education is the foundation that connects knowledge about nutrition and parenting with concrete actions in everyday life. With quality education, we can create a healthy, intelligent generation that is better able to face future challenges. Based on the results of observations in the Nglele village community, especially with one of the integrated health post (Posyandu) cadres in Nglele Village, there is a problem of stunting in Nglele Village, due to several factors, one of which is the lack of insight into the importance of maintaining a balanced diet for the baby. The purpose of this socialization of the importance of balanced nutrition and parenting is to improve the quality of nutrition towards a superior generation in Nglele Village. The methods used in this service are socialization and mentoring methods. Based on the results and discussions of the implementation of community service activities with the socialization of "The Importance of Balanced Nutrition and Parenting as an Effort to Prevent Stunting" in Nglele Village, Sumobito, Jombang, it was concluded that the socialization activity successfully increased community knowledge about the importance of balanced nutrition and the dangers of stunting. Most participants showed high enthusiasm and a good understanding of the material presented. There are indications of behavioral changes in eating patterns and family parenting patterns.